Anaerobic Ammonium Oxidation Performance in Shrimp Pond Wastewater Treatment - Zulkarnaini, Zulkarnaini; Gumelar, Guno; Zainuddin, Elmi (Andalasian International Journal of Applied Science, Engineering and Technology, 2022)
Intensive shrimp culture waste contains high nitrogen, reducing water quality and environmental carrying capacity. Anaerobic ammonium oxidation (anammox) is a potential technology for nitrogen removal. This research aimed to analyze nitrogen removal performance in a filter bioreactor (FtBR). Ammonium and nitrite concentrations of 70-100 mg-N/L were added to sterilized seawater as artificial wastewater and flowed to the reactor with HRT 24-hour. After 120 days of the experiment, the maximum nitrogen removal performance with parameters ACE, NRE, NRR were 82.48%, 72.58%, 0.12 kg-N/m3·d, respectively. The nitrogen stoichiometric ratio NH4+-N:NO2--N:NO3--N was 1:1,40:0,12, which was close to the stoichiometry of anammox process. The anammox process can be a new method for intensive shrimp culture wastewater treatment.